TARJUMĀN AL-MUSTAFĪD: TAFSIR LENGKAP PERTAMA DI NUSANTARA - Zaimul Asror (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper discusses the characteristics, and methods of interpretation of Tarjumān al-Mustafīd. Using the descriptive-analytic method, the study answers the question of how are the characteristics of Tarjumān al-Mustafīd, written by ‘Abd al-Ra’ūf? The writer finds that although the author of this tafsir had served as a mufti during the reign of the Sulṭānah Safiat al-Dīn Tāj al-ʻAlām (1641-1675), but — as far as the writer could observe, no political influence was found in this book of commentary. Moreover, although ‘Abd al-Rā'uf was a mursyīd of the Syattariyah tariqah, he did not give much nuance to his book of tafsir. At the same time, this finding rejects the assumption that Tarjumān al-Mustafīd can be characterized to have sufi nuances in it.